1991
DOI: 10.1002/jhet.5570280454
|View full text |Cite
|
Sign up to set email alerts
|

Competitive free radical 4‐nitrophenylation of pyridine and thiophene

Abstract: Competitive free radical 4‐nitrophenylation of pyridine and thiophene shows a relative reactivity of thiophene:pyridine of 1.3:1 as based on product isolation. A three‐center reaction is proposed to account for the predominance of alpha substitution in each system. Column chromatography and 1H nmr are used for separation and identification of products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
4
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…Klemm and Dorsey studied competitive free radical 4-nitrophenylation of pyridine and thiophene under conditions somewhat more acidic than those used in the present study [9]. They found that thiophene is more reactive than pyridine (in a ratio of 1.3:1) and, in agreement with reports from other workers [10], that substitution alpha to the heteroatom predominates in both rings.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Klemm and Dorsey studied competitive free radical 4-nitrophenylation of pyridine and thiophene under conditions somewhat more acidic than those used in the present study [9]. They found that thiophene is more reactive than pyridine (in a ratio of 1.3:1) and, in agreement with reports from other workers [10], that substitution alpha to the heteroatom predominates in both rings.…”
supporting
confidence: 90%
“…and Dorsey proposed that attack by an electron-seeking free radical (such as 4-nitrophenyl) will occur preferentially at the heteroatom (S or N), where electrons are readily available, but that a rearrangement of the free radical will occur to an alpha position via a three-center reaction mechanism [9,11]. Since the sulfur atom of thiophene should furnish an electron more readily than the nitrogen atom of pyridine one can rationalize the greater reactivity of thiophene.…”
Section: Jan-feb 2001mentioning
confidence: 99%
“…For use of 4-nitroaniline an isomeric selectivity of 24:1 was reported. This compares favorably with other data from the literature [25]. Extending these relationships to 4-nitrophenylation of 1, we expect that the reaction should be kinetically controlled and could well result in markedly different yields of the five possible isomers 3a-3e (as observed).…”
supporting
confidence: 86%
“…38 tron-attracting than 6, Porter has suggested that thiophene might even transfer an electron to a phenyldiazonium cation, with formation of nitrogen gas and a phenyl free radical [20]. Whatever the reaction mechanism might be, the diazonium intermediates from 2-nitro-, 4-nitro-, and 2,4-dinitroanilines all give preferential substitution into the alpha position of thiophene [23][24][25][26].…”
mentioning
confidence: 99%
See 1 more Smart Citation